2009
DOI: 10.1021/ic901372k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Folding Structures Mediated by Metal Coordination of Acyclic Multidentate Ligand

Abstract: Four kinds of folded structures are formed upon the metal complexation of a bis(N(2)O(2)) ligand in which two oxime-type N(2)O(2) chelate ligands are connected by a flexible diethyleneoxy linker. The N(2)O(2) coordination sites are intended for d-block transition-metal ions, and the diethyleneoxy linker can interact with hard metal cations. Meso double helical, folded Omega-shaped, S-shaped helical, and single helical structures were formed depending on the metal combination. The difference in the affinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…We have already demonstrated that a binding selectivity trend of alkali metal << Zn 2+ < alkaline earth < rare earth metal ions was observed in the shorter L 1 Zn2M system [57] and related complexes [79][80][81][82][83] without chiral auxiliary. If the longer L 4 Zn3M system having a chiral auxiliary also shows a similar selectivity trend, Ba 2+ in the L 4 Zn3Ba can be efficiently replaced by La 3+ .…”
Section: Helicity Inversion By Metal Exchangementioning
confidence: 92%
“…We have already demonstrated that a binding selectivity trend of alkali metal << Zn 2+ < alkaline earth < rare earth metal ions was observed in the shorter L 1 Zn2M system [57] and related complexes [79][80][81][82][83] without chiral auxiliary. If the longer L 4 Zn3M system having a chiral auxiliary also shows a similar selectivity trend, Ba 2+ in the L 4 Zn3Ba can be efficiently replaced by La 3+ .…”
Section: Helicity Inversion By Metal Exchangementioning
confidence: 92%
“…On the other hand, because of complex 2 is synthesized by the half-salamo ligand HL 2 , when the Zn(II) atoms coordinated to HL 2 , the conjugate system of complex 2 not change greatly compared with complex 1, which leads to the absorption spectra were almost unchanged before and after the complexation. Upon coordination of the ligand HL 2 , the absorption intensities are weakened compared with the free ligand HL 2 , which indicate that the oxime nitrogen atoms are involved in coordination with the Zn(II) atoms [37,66]. compared with the free ligand HL , which indicate that the oxime nitrogen atoms are involved in coordination with the Zn(II) atoms [37,66].…”
Section: Uv-vis Spectramentioning
confidence: 99%
“…Upon coordination of the ligand HL 2 , the absorption intensities are weakened compared with the free ligand HL 2 , which indicate that the oxime nitrogen atoms are involved in coordination with the Zn(II) atoms [37,66]. compared with the free ligand HL , which indicate that the oxime nitrogen atoms are involved in coordination with the Zn(II) atoms [37,66].…”
Section: Uv-vis Spectramentioning
confidence: 99%
“…Especially, some substitution of atoms of the ligand with other elements often evidently improves its properties. When an O-alkyl oxime unit substitutes the imine moiety, the larger electronegativity of the O atoms is predicted to improve significantly the electronic behaviors of Salamo-type compounds, which may give rise to novel structures and better properties of the metal(II) complexes [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%